Research progress on the role of sulfide in novel biological nitrogen removal processes - CHEN Tao; SHEN Yaoliang (Gongye shui chuli)
Sulfides are common electron donors in the environment and strong inhibitors of some key microorganisms in wastewater biological treatment processes. In this paper, the inhibitory mechanisms and effects of sulfides as inhibitors on denitrification performance in new biological denitrification processes such as partial nitrification-denitrification, anaerobic ammonia oxidation, and mixed nutrient denitrification were summarized. The role of sulfides as electron donors in new biological denitrification processes, sulfide-driven autotrophic denitrification coupling processes, and related combination processes was discussed. The application of sulfide-based wastewater denitrification treatment processes in practical engineering was listed, demonstrating their significant advantages in reducing sludge production and energy demand compared to traditional processes. Finally, the research direction of sulfide-based denitrification was discussed. It was proposed to continue exploring how to cleverly combine it with traditional sewage treatment processes to achieve comprehensive applications in the future, which was of great significance for promoting the continuous progress and optimization of new biological denitrification processes, and achieving efficient, sustainable, and economical wastewater treatment.